Sexting and institutional discourses of child protection: The views of young people and providers of relationship and sex education. (7th July 2021) - York, Leanne; MacKenzie, Alison; Purdy, Noel
Abstract : This article focuses on discourses of child safety and protection of stakeholder organisations (SOs) and school pastoral care co‐ordinators (PCCs) on educating young people about sexting. Individual semi‐structured interviews were conducted with the representatives of four organisations who assist schools in the delivery of Relationships and Sexuality Education (RSE); and with three PCCs in three different types of secondary schools in Northern Ireland to ascertain how their school educates and responds to sexting. Focus groups were also conducted with 17 (10 girls and 7 boys) 16–17‐year‐olds to explore their views on sexting. The results of this study reveal that the predominant discourse in RSE is child safety and protection, and abstention from sexting. The three main groups (young people, SOs and PCCs) vary, however, in how they view sexting behaviour: the stakeholders are largely cautious and counsel against sending sexual pictures, while the young people regard it as normal behaviour. RSE provided by the schools is inadequate and unrealistic, and does not represent what actually goes on in young people's sexual lives. Young people want to be consulted on the content of RSE lessons and resources; and RSE content should desist from telling them not to sext and enable them to explore appropriate relationship behaviours, including sexting. Teachers should feel confident in teaching such material and should have access to appropriate training.